Vaccination against Respiratory Infections in the Immunosenescent Older Adult Population: Challenges and Opportunities - Ecarnot, Fiona; Maggi, Stefania (Seminars in Respiratory and Critical Care Medicine, 2025)
Respiratory infections are associated with a huge burden of disease every year and disproportionately affect older adults, namely those aged 65 years and older. Older adults are at increased risk of infections compared with their younger counterparts, and once infected, have a higher risk of experiencing severe disease course, complications, and long-term sequelae. Therefore, vaccination is clearly a key strategy to prevent infection and its attendant negative consequences. We review here the burden of common respiratory diseases in older adults, namely influenza, pneumococcal disease, and respiratory syncytial virus. We then review some of the challenges facing immunization of older adults, namely immunosenescence, inflammaging, and low vaccine uptake. Next, potential opportunities for overcoming these challenges are reviewed, including the use of higher antigen doses and/or adjuvants in vaccine formulations for older adults, and the potential of multiomics analyses to improve development, performance, and implementation of vaccines.
Keywords: respiratory infection; vaccination; influenza; pneumococcal disease; respiratory syncytial virus; older adults